The Effect of Self Assessment Good Corporate Governance and Risk Management on Financial Performance - Meisya Pebiana; Wulandari, Rosita; Wiwit Irawati; Ali Mubarok (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2024)
This quantitative study examines the impact of The Self Assessment of Good Corporate Governance and Risk Management, proxied by Credit Risk (NPL), Market Risk (NIM), Liquidity Risk (LDR), and Operational Risk (BOPO), on Financial Performance measured by Return on Assets (ROA). The research utilizes secondary data from 29 conventional banking companies listed on the Indonesia Stock Exchange over a 5-year period, generating 145 observation data points from 2018 to 2022. Data analysis employs Eviews 12 for descriptive statistics, model accuracy tests, classical assumption tests, coefficient of determination (R²), panel data linear regression analysis, as well as F and t statistical tests. Findings indicate that both GCG and Risk Management variables collectively influence financial performance based on F-test results. Specifically, t-test results reveal that NIM and BOPO variables partially impact financial performance, whereas GCG, NPL, and LDR variables show no partial effects.